“It is Hard to Think About”: A Mixed-Method Exploration into the Application of the Theory of Compassion Collapse to the #MeToo Movement - Kulp, Simeon (Journal of interpersonal violence, 2023)
After the popularization of #MeToo in 2017, the conversation around sexual violence was brought to global attention. The collapse of compassion theory is proposed to occur in situations where individuals no longer feel increased levels of empathy due to an increase in the number of victims. This theory was employed to attempt to understand negative responses to #MeToo. The current study used a mixed methods exploratory approach to understand how exposure to multiple versus single victim(s) (image(s) and vignette) of sexual violence may affect participants’ perception of survivors of sexual violence. We hypothesized that individuals who were exposed to multiple victims would demonstrate less compassion, higher levels of distance, more diffusion of responsibility, lower perceived efficacy, and less belief of the victim’s story compared to individuals who were exposed to a single victim. We hypothesized that individuals with higher levels of rape myth acceptance (RMA) would endorse greater rates of distance and diffusion, and lower rates of compassion, efficacy, and belief. Participants, recruited via MTurk, were randomized into a single-image group or an eight-image group accompanied by a vignette explaining that the woma(e)n were victim(s) of sexual violence and naming the #MeToo movement. Participants in the single-image group expressed more belief in the victim’s story and endorsed higher levels of psychological distance than the eight-image group. Higher rates of RMA related to less belief and compassion for victims and increased distance. In the qualitative analysis, three content areas were identified: (a) comments on woman(en), (b) comments on #MeToo, and (c) comments on sexual violence. The majority of responses expressed support for the #MeToo movement, with a smaller percentage expressing highly critical views including questions on the inclusivity of #MeToo and sexualization of the woman(en) in the vignettes. Implications and integration of results are discussed.